Design and experimental implementation of skewed stator structured PM generator using Multi-Objective Genetic Algorithm for gearless direct driven wind system - Topaloglu, Ismail; Bektaş, Enes; Yiğit, Mahmud Esad; Korkmaz, Fatih (Ain Shams Engineering Journal, 2024)
This study presents the electromagnetic design, analysis, optimization with Multi-Objective Genetic Algorithm (MOGA) and implementation of a permanent magnet (PM) generator for gearless direct-driven wind turbine applications. The main purposes of this study are to achieve a cost-effective system, create compact design with improved cogging torque and obtain high efficiency design. Two output objective functions (cost and efficiency) are improved by using geometric dimensions parameters of the generator in MOGA optimization. Simulation and experimental results have been compared and obtained as very close to each other. Both the simulations and experimental study have demonstrated that the efficiency of the proposed structure is achieved at the desired level. The efficiency of the wind power system has been improved and hardware cost is reduced via the proposed MOGA-based optimization approach for skewed stator PM generator.